Cognitive flexibility as a protective factor for empathy - Cai, Zhiwei; Qi, Bing (Frontiers in Psychology, 2023)
Many studies have found that empathy can promote prosocial behavior, social relationships, and psychological health, which is vital to society and individuals. However, others have found that the inherent cognitive costs of empathy will motivate people to avoid empathy. While the literature emphasizes the importance of cognitive flexibility as a switching ability for empathy, findings on the relationship between cognitive flexibility and empathy have been inconsistent. Inconsistent results may be because cognitive flexibility is a multi-level structure, while empathy is also a multilayer structure, and there are differences in how researchers define and measure cognitive flexibility. Therefore, the study explores the relationship between cognitive flexibility and empathy from a multi-dimensional perspective. Because of the effect of executive function on empathy, working memory, inhibitory control, gender, and age were additional control variables. This study involved 105 China students aged between 18 and 22 (M age = 20.26, SD = 2.00) who completed the Cognitive Flexibility Scale (cognitive flexibility trait, cognitive flexibility at the individual level), perspective-switching flexibility task (perspective-switching flexibility, cognitive flexibility at the cognitive level), the Interpersonal Reactivity Index scale (IRI, traits empathy), Multi-dimensional Empathy Test (state empathy), 2-back task (inhibitory control), and Stroop task (working memory). After controlling for additional variables, the results showed that: (1) Cognitive flexibility traits negatively predicted trait cognitive (IRI-PT) and affective empathy (IRI-EC). (2) The Other/Self perspective-switching flexibility negatively predicted the affective component of state empathy. (3) Cognitive flexibility traits and Other/Self perspective-switching flexibility negatively predicted empathy even after controlling for one of these. The study's results suggested that cognitive flexibility negatively predicts empathy and is a protective factor for reducing the cost of empathy and promoting emotion regulation.